Once Daily Self-Monitoring of Blood Glucose (SMBG) Improves Glycemic Control in Oral Hypoglycemic Agents (OHA)–Treated Diabetes: SMBG-OHA Follow-Up Study - Harashima, Shin-ichi (J Diabetes Sci Technol, 2015)
BACKGROUND: The aim of this study was to compare glycemic control between SMBG-continued and -discontinued subjects with type 2 diabetes in the SMBG-OHA study. METHOD: Of the 96 subjects from the SMBG-OHA study, 59 were recruited for the 24-week, comparison follow-up study. The study outcomes were the differences in change in HbA1c levels at 24 weeks between the 2 groups, and change in SMBG frequency in SMBG-continued subjects. RESULTS: Although health insurance does not cover the cost of SMBG, 22.0% of subjects continued SMBG of their own will after the SMBG-OHA study was completed. HbA1c levels were maintained from 6.81 ± 0.55% to 6.64 ± 0.53% in SMBG-continued subjects. Conversely, HbA1c levels were increased from 7.18 ± 0.63% to 7.48 ± 0.84% in SMBG-discontinued subjects. HbA1c levels were significantly different by 0.83 ± 0.25% (95% CI: −1.33 to −0.36). The difference in change in HbA1c between the groups was −0.46% (95% CI: −0.78 to −0.15). SMBG frequency was decreased from 2.02 ± 1.06 to 1.53 ± 0.86 times a day. CONCLUSIONS: HbA1c levels were maintained in SMBG-continued subjects but increased in SMBG-discontinued subjects. The study implied that almost once daily SMBG is helpful to maintain glycemic control in non-insulin-treated type 2 diabetes.